HUBUNGAN KONDISI FISIK DAN MEKANISME KOPING INDIVIDU DENGAN HARGA DIRI PENDERITA PASCA STROKE DI POLIKLINIK SARAF RSUD RADEN MATAHER JAMBI - Zarmi Zarmi; Martha Suri; Daryanto Daryanto (Jurnal Akademika Baiturrahim Jambi, 2017)
Background: Chronic diseases such as stroke require changes in behavior patterns that have long been accepted and lived. The more chronic the stroke suffered will disrupt the patient's ability to engage in activities that support a sense of worth or success, which affects the patient's self-esteem. This study aims to determine the relationship of physical conditions and mechanisms of individual coping with self-esteem post-stroke patients in the clinic nerve RSUD Raden Mattaher Jambi. Method: This research is quantitative research with cross sectional method, using accidental sampling technique with sample number 60 respondents. This research was conducted in clinic nerve clinic RSUD Raden Mattaher Jambi from 11 to 28 March 2016 Instrument used questionnaire, analyzed by univariate analysis, bivariate and chi-square test. Results: The results of the analysis of 60 respondents, 42 respondents (70%) with low self-esteem, 11 respondents (18.3%) and 7 respondents (11.7%) with high self-esteem, 37 respondents (61.7% ) With physical condition disorder and 23 respondents (38,3%) without physical condition, 39 respondents (65%) had maladaptive coping mechanism and 21 respondents (35%) had adaptive coping mechanism. The result of statistical test shows that there is a significant correlation between physical condition and coping mechanism with self-esteem of post-stroke patient in RSUD Raden Mataher Jambi. Hospital is expected to increase self-esteem post-stroke patients, and psychological support in stroke patients, because it will greatly affect the coping behavior raised by patients.